Persepsi Masyarakat Mengenai Bangunan Jetty sebagai Bangunan Pengaman Pantai di Pantai Purus Kota Padang - Annisa, Sri Mulya; Hermon, Dedi (AHKAM, 2024)
This study aims to determine the analysis of community perceptions of jetties as coastal safety buildings and the impact of the existence of jetties on community economic activities. The type of research used in this research is qualitative research, using a qualitative approach. This research was conducted in the Purus beach area which is located in West Padang District, Padang City. The sources of information in this research are people who live along the river and who carry out activities at the jetty location. Based on the results of data analysis and discussion, the following two things were obtained. First, community perception influences the level of community awareness to support government efforts in disaster mitigation, namely the construction of coastal safety buildings, namely jetties, where in this area there are two social interactions, namely settlement and community economic activity. It can be seen from the condition of the settlement in Rimbo Kaluang Village which is dirtier compared to the condition of the settlement in Purus Village which is more clean. Second, both old and new traders are of the opinion that the location of the jetty is not ready to be used as a Culinary Market with the number of traders dominating compared to visitors, as well as the decline in income. experienced by old and new traders.